Tell me more: Can a memory test reduce analogue traumatic intrusions? - Krans, J; Näring, G; Holmes, E; Becker, E (2009)
Information processing theories of post-traumatic stress disorder (PTSD) state that intrusive images emerge due to a lack of integration of perceptual trauma representations in autobiographical memory. To test this hypothesis experimentally, participants were shown an aversive film to elicit intrusive images. After viewing, they received a recognition test for just one part of the film. The test contained neutrally formulated items to rehearse information from the film. Participants reported intrusive images for the film in an intrusion diary during one week after viewing. In line with expectations, the number of intrusive images decreased only for the part of the film for which the recognition test was given. Furthermore, deliberate cued-recall memory after one week was selectively enhanced for the film part that was in the recognition test a week before. The findings provide new evidence supporting information processing models of PTSD and have potential implications for early interventions after trauma.